Institutional storytelling and personal narratives: reflecting on the 'value' of narrative inquiry. Issue 2 (3rd April 2018) - O' Toole, Jacqueline
Abstract : With the 'narrative turn', a momentum gathered in the wider social sciences that asserted that listening to, asking for, gathering and analysing stories provided a new impetus to researching human behaviour. The argument evolved: people are storied beings and to generate a more in-depth understanding of people and their experiences, researchers need to begin with their stories. But the stories people tell are also deeply embedded in narrative frameworks and narrative environments that make up what I conceptualise as institutional storytelling. Arguably, institutional storytelling has a profound impact on the stories people can and do tell. Narrative inquiry has much to offer to the analysis of institutional and personal narratives. In this article, I will address the question of the relevance of narrative inquiry to gather and analyse the stories that people and institutions tell. Drawn from an empirical sociological study of women's narratives of their weight management experiences in the context of their participation in weight management classes, I present a case for narrative ethnography as a critical methodological strategy to analyse the complex relationship between institutional and personal narratives.